Effect of food safety training on behavior change of food handlers: A case of orange-fleshed sweetpotato purée processing in Kenya - Malavi, D.N.; Abong, G.O.; Muzhingi, T. (Elsevier, 2020)
Sweetpotato purée processing is new to Kenya and a rapidly growing value addition activity among informal, small, and medium-sized food enterprises (SMEs) in sub-Saharan Africa (SSA). Inadequate knowledge of food safety and poor hygiene practices by food handlers, low level of compliance with Good Manufacturing Practices (GMPs), and microbial contamination are major food safety challenges in orange-fleshed sweetpotato (OFSP) purée processing in Kenya. The extent of food safety training in enhancing food safety in rural-based SMEs and food processing environments has not been fully investigated. This study aimed at evaluating the impact of food safety training on food safety knowledge and hygiene practices of food handlers and in control of microbial contamination in OFSP purée processing in Kenya. Pre- and post-food safety training assessments were conducted to determine food handler's (N = 14) knowledge and practices on food safety. Food, water, and swab samples (n = 62) from the processing environment were collected before and two months after the training and analyzed for food hygiene indicator microorganisms. The findings indicate a significant (p < 0.05) improvement in overall food safety knowledge and practices of food handlers after the training. Poor knowledge scores were exhibited on aspects of cross-contamination, cleaning, and sanitation but these significantly (p < 0.05) improved after the training. Similarly, microbial counts on food equipment surfaces, installations, personnel hands, and in the final product (OFSP purée) significantly (p < 0.05) declined to acceptable levels after the food safety training. Total counts, yeasts and molds, S. aureus, Enterobacteriaceae, and total coliforms counts in the packaged OFSP purée were 2.6, 1.8, 1.5, 1.9, and 1.2 LOG CFU/g respectively hence suitable for its current application as an ingredient in baked products. The findings from this study indicate food safety training as an appropriate tool for improving food handler's knowledge and hygiene practices as well as enhancing microbial safety and quality of processed foods in SMEs if necessary food safety support resources are provided.